Marine hybrid hotspot at Indo-Pacific biogeographic border - Hobbs, Jean-Paul; Frisch, A.; Allen, G.; Van Herwerden, L. (Royal Society Publishing, 2009)
Studying hybridization is crucial to understanding speciation and almost all our knowledge comes from terrestrial and freshwater environments. Marine hybrids are considered rare, particularly on species-rich coral reefs. Here, we report a significant marine hybrid zone at Christmas and Cocos Islands (eastern Indian Ocean) with 11 hybrid coral reef fishes (across six families); the most recorded hybrids of any marine location. In most cases, at least one of the parent species is rare (less than three individuals per 3000?m2), suggesting that hybridization has occurred because individuals of the rare species have mated with another species owing to a scarcity of conspecific partners. These islands also represent a marine suture zone where many of the hybrids have arisen through interbreeding between Indian and Pacific Ocean species. For these species, it appears that past climate changes allowed species to diverge in allopatry, while recent conditions have facilitated contact and subsequent hybridization at this Indo-Pacific biogeographic border. The discovery of the Christmas–Cocos hybrid zone refutes the notion that hybridization is lacking on coral reefs and provides a natural laboratory for testing the generality of terrestrially derived hybridization theory in the marine environment.